Konstruktion einer Anleihe mit hypothekarischer Besicherung - Johannes Alram (Frankfurt School of Finance & Management, 2009)
This work describes the legal structuring of a mortgage covered bond in accordance with the regulations of paragraphs 791 cont. and 1184 cont. German Civil Code (Bürgerliches Gesetzbuch). The work shows how to structure the share of common rights of the bond holders according to the regulations of the German Statue Governing Common Rights of Owners of Debt Securities (Schuldverschreibungsgesetz). Furthermore, the work describes how the bond creditors shall have preferences of the mortgages in case of default of the bond and how mortgages shall be limited through lending limit in relation to the market value decline of the real estate building. The market value determination will follow the regulations of paragraph 192 cont. German Building Act (Baugesetzbuch) in connection to the German Value Determining Regulations (Wertermittlungsverordnung). The legal aspects are embodied and tightened in the bond terms which are included in the work. The paper also points out which minimum information of the mortgage covered bond in a prospectus is required. The Federal Financial Supervisory Authority (Bundesaufsichtsamt für Finanzdienstleistungen) scrutinises the prospectus for admission to public offering according to the regulations of the German securities prospectus act (Wertpapierprospektgesetz). Finally, the usability of a recovery rating which measures the probability of default of the mortgages is discussed in the paper.
urn:nbn:de:101:1-20090420303
Keywords: K12; K19; K22; K29; 330; Grundbuch- und Gläubigervertretung; Deckung von Hypotheken; Investmentgesetz; Schuldverschreibungsgesetz; Anleihe; Bond; Recovery Rating; Versicherungsaufsichtsgesetz; (Wertpapier-)(Sicherungs-) Hypothek; Wertpapierprospektgesetz; Mortage backed securities